Analysis of Leadership Behave And Career Development - Angga Karta Puspito; Alfatih Sikki Manggabarani; Desmintari (Yayasan Ilomata, 2020)
This research was conducted to analyze the effect of training, work culture, leadership behaves on the intention of career development of Kantor Imigrasi Kelas I Khusus non-TPI Jakarta Barat. The research sample used was 40 respondents consisting of Kantor Imigrasi Kelas I Khusus non-TPI Jakarta Barat section employees, namely between the Services and Verification of Travel Document, Intelligence, and Investigation Operation, Stay Permit and Immigration Status and Citizenship, Immigration Information System and Technology, Human Resources and Administration. Data analysis in this study using PLS analysis using PLS version 3.2.8 software The results show that training had no significant on career development, training had no significant effect on leadership behave, work cultural had no significant effect on career development, work cultural had no significant effect on career development, leaderships behave had a significant effect on career development on Kantor Imigrasi Kelas I Khusus Non-TPI Jakarta Barat Based on the results of the research conducted, the variable leaderships behave has the most important role because it becomes an intervening variable, which connects training variables to career development variable and works cultural variable to career development variable.